Life cycle of oil palm bagworm, Metisa plana walker (Lepidoptera : Psychidae) at different temperatures under controlled environment - Cynthia Eja Enting; Siti Noor Hajjar Md Latip (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Temperature is one of the most important abiotic factors that affects insect life cycle. Unpredictable local climate changes in Malaysia had caused the outbreak of bagworm, Metisa plana for over five decades. This had led to a major problem of oil palm yield production. Hence, it is significant to study the nature of this pest especially their life cycle to prevent further outbreak. This study is expected to provide M. plana surveillance program planning that can prevent massive damage of defoliation from occurring. The application to control bagworms should be applied at the right time especially during the crucial climate changes that could trigger the bagworm’s life cycle. The main objective in this study is to evaluate the life cycle of oil palm bagworm, M. plana in different degrees of temperature. This study was conducted under controlled conditions in the laboratory from October 2017 until October 2018 with different ranges of temperature between 16°C to 40°C. The duration in days from egg to adult was observed and recorded daily. This study found that bagworms were able to adapt and complete life cycles at a selected temperature between 20°C to 36°C, but did not survive at 16°C and 40°C. The duration observed of the completed life cycle of this species significantly decreased with the increase in temperature. The duration in days of the completed life cycle of temperature at 20ºC, 24ºC, 27.5ºC, 32ºC and 36ºC was approximately about 122.2±0.87, 108.4±1.74, 99.6±1.89, 81.2±1.70 and 64.8±1.25 respectively. The optimum temperature of bagworm’s survival rate was at 32°C with a total percentage at 63.48%. This study provides basic fundamental information on the life cycle of bagworm, M. plana especially for oil palm growers. Hence, growers will have better pest management plans to control this bagworm species related to different temperatures and prevent yield loss of fresh fruit bunch (FBB) of oil palm plantation per acre.